Slowing of Event-Related Potentials in Primary Progressive Aphasia. A case report - Salvatore Giaquinto; Francesca Ranghi (The Scientific World Journal)
Primary Progressive Aphasia (PPA) is a rare and insidious language impairment that worsens over time. It belongs to the group of fronto–temporal dementias. This study was aimed at assessing the role of speed of cognitive abilities, such as word recognition, in PPA. The design is a single-case, longitudinal study. A male patient suffering from PPA was enrolled and 15 healthy older adults were the control group. An event-related electrical potential connected with word recognition, namely the N400, was delayed by 200 msec at baseline compared to healthy controls and progressively deteriorated. One year later, the delay was greater and two years later the potential had disappeared. Reduced speed of processing is an early pathological factor that negatively affecting higher cognitive functions in APP. Event–related electrical potentials are recommended in the field of aphasia and cognitive decline. They permit observation of a speed decline in higher cognitive abilities, when pathological changes at a central level begin and language comprehension seems to be unaffected.